Can AI Ever Control us Humans: A Probe - Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2023)
Two interrelated thesis are explored in this probe, namely that;i. AI by itself could never take over and control us humans;ii. the written word is in a certain sense a form of artificial intelligence whereas the spoken word is a form of natural intelligence.